2019
DOI: 10.1002/ece3.5132
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear microsatellite and mitochondrial DNA analyses reveal the regional genetic structure and phylogeographical history of a sanguivorous land leech, Haemadipsa japonica, in Japan

Abstract: Recent molecular studies have indicated that phylogeographical history of Japanese biota is likely shaped by geohistory along with biological events, such as distribution shifts, isolation, and divergence of populations. However, the genetic structure and phylogeographical history of terrestrial Annelida species, including leech species, are poorly understood. Therefore, we aimed to understand the genetic structure and phylogeographical history across the natural range of Haemadipsa japonica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…1, 2). This boundary is similar to that observed in a haemadipsid leech in Japan that is attributed to the expansion from northern and southern refugia (Morishima and Aizawa 2019).…”
Section: Discussionsupporting
confidence: 85%
“…1, 2). This boundary is similar to that observed in a haemadipsid leech in Japan that is attributed to the expansion from northern and southern refugia (Morishima and Aizawa 2019).…”
Section: Discussionsupporting
confidence: 85%
“…1). Therefore, this study provides additional distribution records of this species well beyond its original known range; only trignathous Haemadipsa leeches have previously been recorded in the Far East (Lai et al ., 2011; Seo et al ., 2013; Morishima and Aizawa, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex PCR were performed by using methods described elsewhere (Morishima & Aizawa, 2019). Genotypes were determined by using an ABI 3500 Genetic Analyzer and GeneMapper ver.…”
Section: Nuclear Microsatellite Genotypingmentioning
confidence: 99%
“…In Tochigi Prefecture, the sika deer distribution ranges from the northwestern to the southwestern regions (Figure 2; Tochigi Prefecture, 2017) and overlaps with the H. japonica distribution range found in both the northern and southern regions (Figure 1). However, a previous study using H. japonica microsatellite markers showed that limited mobility likely resulted in marked genetic differentiation and reduced gene flow between populations (Morishima & Aizawa, 2019). Similar regional genetic differentiation was also found in other leech species in Cambodia (Tessler et al, 2018), suggesting that leeches do not move a lot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation